The Success Story of Gold-Based Catalysts for Gas- and Liquid-Phase Reactions: A Brief Perspective and Beyond - Price, Cameron A. H.; Pastor-Pérez, Laura; Ivanova, Svetlana; Reina, Tomas R.; Liu, Jian (Frontiers in Chemistry, 2019)
Gold has long held the fascination of mankind. For millennia it has found use in art, cosmetic metallurgy and architecture; this element is seen as the ultimate statement of prosperity and beauty. This myriad of uses is made possible by the characteristic inertness of bulk gold; allowing it to appear long lasting and above the tarnishing experienced by other metals, in part providing its status as the most noble metal.